2021
DOI: 10.51253/pafmj.v71isuppl-3.7228
|View full text |Cite
|
Sign up to set email alerts
|

Hypocalcemia in Total Versus Subtotal Thyroidectomy

Abstract: Objective: To compare the occurrence of hypocalcemia in patients undergoing subtotal and total thyroidectomy. Study Design: Comparative prospective study. Place and Duration of Study: Surgical departments of Ayub Teaching Hospital, Abbottabad and Combined Military Hospital, Rawalpindi, from Mar 2018 to Feb 2020. Methodology: A total of 171 patients were selected for this study and they were divided into 2 groups. Group 1 consisted of 95 patients undergoing Total thyroidectomy whereas group 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Clinical validation seeks to establish a meaningful association between a biomarker and the disease, determining the biomarker’s utility and usefulness in a clinical context. This validation process often involves external validation through retrospective analysis of clinical trial data or prospective clinical trials [ 24 ]. AI and machine learning algorithms are instrumental in integrating diverse data types, expediting the process of biomarker discovery and validation, streamlining drug development, and ultimately enhancing patient outcomes [ 25 - 27 ].…”
Section: Reviewmentioning
confidence: 99%
“…Clinical validation seeks to establish a meaningful association between a biomarker and the disease, determining the biomarker’s utility and usefulness in a clinical context. This validation process often involves external validation through retrospective analysis of clinical trial data or prospective clinical trials [ 24 ]. AI and machine learning algorithms are instrumental in integrating diverse data types, expediting the process of biomarker discovery and validation, streamlining drug development, and ultimately enhancing patient outcomes [ 25 - 27 ].…”
Section: Reviewmentioning
confidence: 99%
“…Maceration are divided in three typesa) Simple maceration b) Double maceration c) Triple maceration [31] Procedure:…”
Section: These Constituents Are Essential For Pharmacological Activit...mentioning
confidence: 99%
“…According to the authors, the incidence of RLN injury is higher in total thyroidectomy compared to subtotal which is 7.2% and 1.9%, respectively. However, a non-randomized controlled trial study Sajid et al was done in 2016 on 177 patients in Rawalpindi to compare between total and subtotal thyroidectomy in terms of RLN injury (44). The incidence of RLN injury in total thyroidectomy is 2.3% compared to 3.3% in subtotal one.…”
Section: Recurrent Laryngeal Nerve Injury In Total Thyroidectomymentioning
confidence: 99%
“…Although many procedures have been introduced to prevent the nerve injury, the incidence of recurrent laryngeal nerve palsy varies between 1.5-14% (43). A randomized controlled trial was conducted on 90 patients of subtotal thyroidectomy at the surgery and Ear Nose and Throat department of Ayub Teaching Hospital Abbottabad and Combined Military Hospital Rawalpindi between 2013 and 2014 (44). The patients had preoperative indirect laryngoscopy examination repeated postoperatively to check for injury to the recurrent laryngeal nerve and showed that only three patients have developed recurrent laryngeal nerve injury (3.3%).…”
Section: Recurrent Laryngeal Nerve Injury In Subtotal Thyroidectomymentioning
confidence: 99%